The Role of Oxytocin Massage in Reducing Stress and Anxiety in Postpartum Mothers - Partiwi, Nur (Advances in Healthcare Research, 2025)
Purpose: This study aims to explore the role of oxytocin massage in reducing stress and anxiety among postpartum mothers while enhancing breastfeeding success. This study investigates the efficacy of oxytocin massage as a non-pharmacological intervention to enhance maternal well-being and lactation outcomes. Research Method: This study employed a systematic literature review (SLR) approach, analyzing peer-reviewed articles published after 2018 from reputable databases, including Elsevier, Emerald, Wiley, and Springer. Inclusion criteria focused on studies examining oxytocin massage and its impact on postpartum stress, anxiety, and breastfeeding success. Data were synthesized and analyzed thematically to identify patterns and gaps in the literature. Results and Discussion: The findings revealed that oxytocin massage significantly reduces postpartum stress and anxiety by stimulating the release of oxytocin, which in turn decreases cortisol levels and promotes relaxation. The oxytocin massage also enhances the milk ejection reflex, thereby facilitating successful breastfeeding. Oxytocin massage emerged as an effective, non-invasive intervention for postpartum care.   Implications: The findings of this study emphasize the importance of incorporating oxytocin massage into standard postpartum care practices, both in clinical settings and at home. Health care providers should be trained to educate mothers about proper massage techniques to ensure optimal benefits.